An exploration of a beginning undergraduate music student conducting with expressivity - Wimmer, Alexander (Kansas State University, 2017)
One of the most important roles of a conductor is to prepare an ensemble to perform, not only accurately but expressively, utilizing physical gestures and facial expressions. For many music students, the development of physical gestures that elicit expressive performance are typically introduced in a beginning undergraduate conducting course. This is important in establishing a framework for understanding the technical aspects of conducting, considering that many beginning student conductors lack a basic comprehension of conducting fundamentals. However, the interpretative and expressive principles of conducting are equally important as basic technique and are often more difficult to teach to undergraduate students. There is an overwhelming amount of gestural skill that should be experienced and explored by a beginning undergraduate conductor. Despite a students’ best efforts in the classroom and in the practice room, expressive conducting skills that represent internal musical intentions remain a primary challenge with novice conducting students. The purpose of this study was to explore the experiences of a beginning undergraduate conductor as they learned to conduct and develop their considerations and skills of conducting to elicit expression. Through case study, exploring the experiences of an undergraduate music student enrolled in a beginning conducting course from a Midwestern university exposed valuable information that could become helpful when designing instruction. The findings addressed the research questions of the study and revealed additional aspects of the learning experience from the perspective of the participant. Through reflection, navigation of self, guided video elicitation, discussion of expressive conducting, and acknowledgement of prior musical expectations and intent, the participant discovered the differences between their perceived expressive gestures and the realization of an audible response from an ensemble.
Keywords: Conducting, Expressivity, Undergraduate Beginning Conductors, Video Elicitation, Journaling, Narrative